Transformações tecnológicas no trabalho de jornalistas 60+ do Estado de São Paulo: um estudo na perspectiva CTS - Savenhago, Igor José Siquieri (Universidade Federal de São Carlos, 2023)
The arrival of the internet in journalistic newsrooms in the 1990s marked changes in production routines, influencing working conditions. A process that required special attention from elderly professionals, given the need for rapid adaptations to mastering technological artifacts, and which was intensified with the Covid-19 pandemic, which forced many of them to telework. Under a multi and interdisciplinary approach, which brings together thoughts from Social Psychology, Sociology, Anthropology, Philosophy, History, Gerontology, Education, Communication, among other fields of Human Sciences, this study observes 60+ resident journalists as journalists and/or who work in the intermediate geographic regions of Ribeirão Preto and São Paulo, in the state of São Paulo, Brazil, build shared visions about these technological transformations and how such representations indicate behaviors related to the exercise of the profession, work relations and the aging process itself. The research was developed in the Postgraduate Program in Science, Technology and Society (PGPSTS) at the Universidade Federal de São Carlos (UFSCar), in the line of research in Social Dimensions of Science and Technology, from a social constructivism perspective. – which finds relevance in Social Studies in Science and Technology (SSST), in which the STS movement is inserted –, and in the light of the Theory of Social Representations (TRS). After a bibliographical review, with a survey of the state of the art of scientific knowledge on technological transformations for the work of journalists, with a focus on older people –, in addition to documentary research, on open public data platforms –, the approach, which is part of the assumptions of social, qualitative research, of an exploratory-descriptive nature, proposes, considering the ethical guidelines for research in Human Sciences, to analyze, with the help of the free software Iramuteq, synchronous individual online reflective interviews carried out with 13 professional journalists 60+ from the aforementioned regions. The sessions, recorded and transcribed, and validated by the participants, made it possible to outline an understanding, via Content Analysis (CA), about the construction and circulation of social representations relating to the mentioned aspects. As a result, it was possible to perceive that the transformations in Journalism based on digital technologies leave professional journalists in a vulnerable condition, which demands a protection network that helps them resolve a process of instabilities and uncertainties.
Technological transformations in the work of journalists 60+ in the State of São Paulo: a study from the STS perspective
Keywords: Jornalista; Tecnologias digitais; Trabalho; Pessoa idosa; Representações sociais; Journalist; Digital technologies; Work; Elderly; Social representations; CIENCIAS HUMANAS; CIENCIAS SOCIAIS APLICADAS::COMUNICACAO; CIENCIAS SOCIAIS APLICADAS::COMUNICACAO::JORNALISMO E EDITORACAO; CIENCIAS SOCIAIS APLICADAS::COMUNICACAO::TEORIA DA COMUNICACAO; CIENCIAS SOCIAIS APLICADAS::COMUNICACAO::JORNALISMO E EDITORACAO::TEORIA E ETICA DO JORNALISMO; OUTROS::CIENCIAS SOCIAIS; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA SOCIAL::PROCESSOS GRUPAIS E DE COMUNICACAO; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA SOCIAL